2010
DOI: 10.1243/09576509jpe984
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis and Optimization of a Gas Turbine Cycle Integrated with an Internal Combustion Wave Rotor

Abstract: In an effort to answer the current needs for more performing and energy efficient gas turbine engines, unsteady pressure gain devices are currently under great focus. This article describes the performance analysis of a novel turbine engine utilizing an internal combustion wave rotor. The performance of this engine is compared to that of a conventional engine, first using its original bypass ratio—fan pressure ratio configuration, and then an optimized configuration. The novel cycle engine is found to be more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Currently, wave rotor technology has been successfully applied in the gas turbine top cycle, [9][10][11] gas expansion refrigeration cycle, [12][13][14] and some other elds. [15][16][17] As an important component of wave rotor technology, GWEs have been investigated by several scientic research institutions, as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, wave rotor technology has been successfully applied in the gas turbine top cycle, [9][10][11] gas expansion refrigeration cycle, [12][13][14] and some other elds. [15][16][17] As an important component of wave rotor technology, GWEs have been investigated by several scientic research institutions, as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that integrating pressure gain combustion (PGC) into gas turbine engines (GTEs) has the potential to increase GTE efficiency and reduce fuel consumption [1][2][3]. Petters and Felder [4] modeled a turbofan with an embedded PGC combustor.…”
Section: Introductionmentioning
confidence: 99%
“…This potentially counteracts the benefit of using PGC. While it is promising that PGC can be integrated into a gas turbine engine without a measurable decrement, the gains predicted by Jones and Paxson [5] and others [1][2][3][4] have not yet be realized. If the predicted gains cannot be realized, there is no reason to use PGC over conventional combustion technology.…”
Section: Introductionmentioning
confidence: 99%
“…The application range for wave rotors outlined by literature is diverse. The bulk of early studies focused on pressure exchangers with straight passage profiles for gas turbine topping cycles [1][2][3][4][5][6][7][8] and supercharging devices for internal combustion engines [9][10][11][12][13][14][15][16]. In recent years the application to refrigeration cycles [17][18][19] and pressure-gain combustors [20][21][22] has come into the focus of consideration.…”
Section: Introductionmentioning
confidence: 99%